2013
DOI: 10.1111/vop.12073
|View full text |Cite
|
Sign up to set email alerts
|

Suture anchor placement technique around the insertion of the ventral rectus muscle for the replacement of the prolapsed gland of the third eyelid in dogs: 100 dogs

Abstract: The suture anchor placement technique provides a cosmetic, rapid, and successful replacement of the prolapsed gland of the third eyelid in dogs. No recurrences were noted. Complications were easily addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
47
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(55 citation statements)
references
References 3 publications
7
47
1
Order By: Relevance
“…Neither in this study nor in the literature was any statistically significant difference found between the number of left and right eyes affected. In our study, both eyes were involved in 19% of dogs, similar to the data in the literature …”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Neither in this study nor in the literature was any statistically significant difference found between the number of left and right eyes affected. In our study, both eyes were involved in 19% of dogs, similar to the data in the literature …”
Section: Discussionsupporting
confidence: 90%
“…The most common breeds present in this study are similar to those previously published in the international literature . The high percentage of cross‐breeds in our study may be due to their high popularity (44.13% of all dogs) in our region.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations